Transforming growth factor-beta activity is potentiated by heparin via dissociation of the transforming growth factor-beta/alpha 2- macroglobulin inactive complex (The Rockefeller University Press, 1989)
The control of smooth muscle cell (SMC) proliferation is determined by the combined actions of mitogens, such as platelet-derived growth factor, and the opposing action of growth inhibitory agents, such as heparin and transforming growth factor-beta (TGF-beta). The present studies identify an interaction between heparin and TGF-beta in which heparin potentiates the biological action of TGF-beta. Using a neutralizing antibody to TGF-beta, we observed that the short term antiproliferative effect of heparin depended upon the presence of biologically active TGF-beta. This effect was observed in rat and bovine aortic SMC and in CCL64 cells, but not in human saphenous vein SMC. Binding studies demonstrated that the addition of heparin (100 micrograms/ml) to medium containing 10% plasma-derived serum resulted in a 45% increase in the specific binding of 125I-TGF-beta to cells. Likewise, heparin induced a twofold increase in the growth inhibitory action of TGF-beta at concentrations of TGF-beta near its apparent dissociation constant. Using 125I-labeled TGF-beta, we demonstrated that TGF-beta complexes with the plasma component alpha 2- macroglobulin, but not with fibronectin. Heparin increases the electrophoretic mobility of TGF-beta apparently by freeing TGF-beta from its complex with alpha 2-macroglobulin. Dextran sulfate, another highly charged antiproliferative molecule, but not chondroitin sulfate or dermatan sulfate, similarly modified TGF-beta's mobility. Relatively high, antiproliferative concentrations of heparin (1-100 micrograms/ml) were required to dissociate the TGF-beta/alpha 2-macroglobulin complex. Thus, it appears that the antiproliferative effect of heparin may be partially attributed to its ability to potentiate the biological activity of TGF-beta by dissociating it from alpha 2-macroglobulin, which normally renders it inactive. We suggest that heparin-like agents may be important regulators of TGF-beta's biological activity.